Implementation of school-based management in Indonesia - Vernez, Georges; Karam, Rita; Marshall, Jeffery H. (Rand Corporation monograph series., 2012)
"This study provides a quantitative and qualitative status report on the implementation of school-based management (SBM) in Indonesia, identifies factors associated with the successful practices of SBM, and assesses SBM effects on student achievement eight years after its inception. The authors' findings are based on face-to-face surveys of principals, teachers, school committee members, and parents; surveys of district staff; and a case study. SBM required a major shift in how people think about schooling and a significant improvement in the capacity of principals, teachers, and the community to provide leadership, develop programmatic alternatives to meet local educational needs, and engage parents and the community in the governance of schools. Implementation of SBM so far has met with limited success. Although most principals reported that they had the autonomy to make school decisions, they also said that they did not take advantage of it by making significant programmatic and instructional changes. Districts continued to strongly influence school policies and practices. School committee and parental involvement in school affairs was minimal. Both expressed an attitude of noninterference with school matters and deference to school staff. All school-level stakeholders said that they were not well prepared to provide effective leadership. Improving implementation and the outcomes of SBM in Indonesia will require expanding principal, teacher, and school committee member capacity to implement SBM; increasing school staff ability to make operational and instructional changes; and developing district capacity to support schools and SBM"--Publisher's website.